PENDEKATAN KOMUNIKATIF DALAM PEMBELAJARAN BAHASA INDONESIA UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SISWA DI KELAS IV SD - Asiah, Asiah (Universitas Pendidikan Indonesia, 2015)
This research aims to improve students' skills in speaking. Researchers apply a communicativeÂ approach through Classroom Action Research. Based on the results of research, learning Indonesian with the application of communicative approach showed an increase in the students' speaking skills class IV SDN Jatiroke I both orally and in writing. This increase can be seen from the observation and implementation of corrective actions at each cycle. First cycle which scored above 60 KKM there are 16 students (61.53%) with an average grade 62.30 increase significantly in the second cycle to 25 students (96.15%) with an average grade of 80.Keywords: approach, communicative skills, speaking, elementary school students.